Elderly Healthy and Productive in Era Pandemic - Rya Anastasya Siregar (IJCS: International Journal of Community Service, 2022)
Old age is an unavoidable aging process, humans grow old through process which at first started from baby, children, teenager, mature and next Becomes old. All People will certainly experience the process of getting old and this is the most important period of human life end. The size amount population elderly in Indonesia in time front bring impact positive nor negative. Positive impact, if the elderly population is in a healthy, active and productive condition. On the other hand, the large number of elderly people becomes a burden if the elderly have a decline problem health which caused on enhancement cost service health, drop income/income, increase in disability, lack of adequate social and environmental support no friendly to population elderly. Method which worn with To do survey and interviews for data collection, data analysis, data presentation, formulating discussions and Furthermore, communication, information and education (IEC) is given using 2 methods, namely: online by using applications including SMS, zoom, WA and other applications. And how direct that is stage counseling with obey protocol health.